Intrahepatic Reactive Lymphoid Hyperplasia: A Case Report and Review of the Literature - Samantha Seitter (Case Reports in Surgery, 2018)
Introduction. Reactive lymphoid hyperplasia (RLH) is a rare and benign lesion found in organs of the gastrointestinal tract, skin, lung, orbit, and more rarely in the liver. Due to its similar appearance on imaging, it is hard to differentiate from primary liver malignancies. The following is a case report of a patient presenting with a suspicious liver lesion found to be RLH associated with primary biliary cirrhosis (PBC), after surgical resection. Presentation of Case. A 54-year-old woman presented with nonspecific abdominal pain, and her workup included axial imaging of the abdomen that showed a suspicious lesion in her liver. After an extensive workup, which included a percutaneous biopsy, failed to confirm a diagnosis, a laparoscopic surgical resection was recommended. Discussion. RLH is a rare condition of the liver, presenting in a suspicious fashion and raising concerns for a primary liver malignancy. RLH should be considered in the differential diagnosis of small hepatic lesions in middle-age females in the absence of any significant risk factors for hepatocellular carcinoma (HCC). RLH tends to be associated with PBC of the liver. Conclusion. RLH of the liver is a rare, hard to diagnose, benign lesion. When intrahepatic, it cannot be easily differentiated from primary liver tumors and frequently requires surgical resection for pathological diagnostic confirmation.